Sex-Biased Parental Investment among Contemporary Chinese Peasants: Testing the Trivers-Willard Hypothesis - Luo, Liqun; Zhao, Wei; Weng, Tangmei (Frontiers in Psychology, 2016)
The Trivers-Willard hypothesis predicts that high-status parents will bias their investment to sons, whereas low-status parents will bias their investment to daughters. Among humans, tests of this hypothesis have yielded mixed results. This study tests the hypothesis using data collected among contemporary peasants in Central South China. We use current family status (rated by our informants) and father's former class identity (assigned by the Chinese Communist Party in the early 1950s) as measures of parental status, and proportion of sons in offspring and offspring's years of education as measures of parental investment. Results show that (i) those families with a higher former class identity such as landlord and rich peasant tend to have a higher socioeconomic status currently, (ii) high-status parents are more likely to have sons than daughters among their biological offspring, and (iii) in higher-status families, the years of education obtained by sons exceed that obtained by daughters to a larger extent than in lower-status families. Thus, the first assumption and the two predictions of the hypothesis are supported by this study. This article contributes a contemporary Chinese case to the testing of the Trivers-Willard hypothesis.